2022
DOI: 10.7150/ijms.73080
|View full text |Cite
|
Sign up to set email alerts
|

The influence of cerebral small vessel diseases on the efficacy of repositioning therapy and prognosis of benign paroxysmal positional vertigo

Abstract: Background: Although vascular risk factors have been found to be closely related to the development of benign paroxysmal positional vertigo (BPPV), the relationship between BPPV and cerebral small vessels diseases (CSVDs) has rarely been discussed in literature. This study set out to investigate the efficacy of repositioning therapy and prognosis among BPPV patients with CSVDs. Methods: We enrolled 553 BPPV patients who had undergone brain MRI, and categorized them into two groups based on the presence or abse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 53 publications
0
4
2
Order By: Relevance
“…In contrast to the current study, Zang et al. 25 showed that residual dizziness was not linked to gender. The disagreement with the present results may be explained by differences in sample sizing and environmental factors.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to the current study, Zang et al. 25 showed that residual dizziness was not linked to gender. The disagreement with the present results may be explained by differences in sample sizing and environmental factors.…”
Section: Discussioncontrasting
confidence: 99%
“…However, after menopause, the effects of sex hormones decrease, and gender differences in residual dizziness decrease. 24 In contrast to the current study, Zang et al 25 showed that residual dizziness was not linked to gender. The disagreement with the present results may be explained by differences in sample sizing and environmental factors.…”
Section: Discussioncontrasting
confidence: 99%
“…Ischemia of the neuroepithelium of the utricular macula or semicircular canals may facilitate their degeneration with consequent detachment of otoliths (17). Indeed, vascular risk factors have been reported to be closely related to the occurrence and prognosis of BPPV (18). Considering that the labyrinthine artery of the inner ear is a tiny terminal artery, small vessel lesions that directly damage the tiny arteries of the inner ear may lead to microcirculation disorders, which could cause damage to the blood vessels of the inner ear and lead to shedding of otoliths (18).…”
Section: Pathophysiology Of Bppvmentioning
confidence: 99%
“…Indeed, vascular risk factors have been reported to be closely related to the occurrence and prognosis of BPPV (18). Considering that the labyrinthine artery of the inner ear is a tiny terminal artery, small vessel lesions that directly damage the tiny arteries of the inner ear may lead to microcirculation disorders, which could cause damage to the blood vessels of the inner ear and lead to shedding of otoliths (18). Patients with hypertension, obesity, and diabetes may also have reduced capillary density that negatively affects microvascular tissue perfusion (19).…”
Section: Pathophysiology Of Bppvmentioning
confidence: 99%
See 1 more Smart Citation